Pengaruh Kombinasi Metode Bobath dan Neurosensomotor untuk Peningkatan Postural Kontrol Duduk pada Delay - TITIN KARTIYANI M.Or (Pena Medika Jurnal Kesehatan, 2021)
ABSTRACT In this case of growth and development, the prevalence of significant growth retardation in the pediatric population is not yet clear. Through statistical calculations, 2-3% of infants are outside the range of normal motor milestones. Of this number, a small proportion (15-20%) are known to have a diagnosis of significant growth and development disorders in the form of cerebral palsy or defects at birth. A child's growth and development disorder, commonly known as Delay Development, is a disorder that attacks the child's growth and development process, in this case, a child's growth and development disorders such as cognitive, gross motoric, fine and emotional. The purpose of this study was to determine whether there is an effect of a combination of bobath exercise and neurosensomotor on sitting postural control on developmental delay. This research is a pre-experimental design, with a one group pretest-post test design. After the difference test between pre-test data and post-test data using Paired T-test, the results were p = (p